Feminism in the news : representations of the women's movement since the 1960s - Mendes, Kaitlynn, 1983- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'An exploration of the representations of the women's movement, its members, and their goals between 1968 and 2008 in the British and American press. Examining over 1100 news articles, the book analyses the nuanced ways feminism has historically been supported, marginalized and debated in the mainstream press'--
Includes bibliographical references and index.
Keywords: Feminism and mass media